1998
DOI: 10.1007/s005350050099
|View full text |Cite
|
Sign up to set email alerts
|

Circulating vascular endothelial growth factor (VEGF) is a possible tumor marker for metastasis in human hepatocellular carcinoma

Abstract: Vascular endothelial growth factor (VEGF) is closely related to angiogenesis in various human cancers. However, little is known of its circulating levels in hepatocellular carcinoma (HCC). We examined circulating VEGF levels in chronic liver disease to assess their clinical significance. Plasma VEGF concentrations were determined, by enzyme immunoassay, in patients with chronic hepatitis (CH; n = 36), liver cirrhosis (LC; n = 77), and HCC (n = 86) for a cross-sectional study. Plasma VEGF levels in healthy cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
63
1
3

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(73 citation statements)
references
References 20 publications
6
63
1
3
Order By: Relevance
“…previous reports by Jinno et al (38) indicated that serum VeGF levels increased gradually along with disease progression in patients with hepatitis, cirrhosis and HCC. there was a significant difference in the level of serum VEGF between HCC and other patient groups, but not among hepatitis patients, cirrhotic patients and normal controls.…”
Section: Serum Levels Of E-cadherin Icam-1 Mmp-2 Vegf Opnmentioning
confidence: 84%
“…previous reports by Jinno et al (38) indicated that serum VeGF levels increased gradually along with disease progression in patients with hepatitis, cirrhosis and HCC. there was a significant difference in the level of serum VEGF between HCC and other patient groups, but not among hepatitis patients, cirrhotic patients and normal controls.…”
Section: Serum Levels Of E-cadherin Icam-1 Mmp-2 Vegf Opnmentioning
confidence: 84%
“…The tumor enhancement degree could also truly reflect the distribution characteristics of tumor microvessels within a tumor mass, as the area with the greatest enhancement was often associated with the highest MVD. Higher tumor MVD was shown to be associated with worse degree of [4,10] , thus it is possible to estimate the biological behaviors of HCC in terms of aggressiveness and metastasis by calculating the parameters of HCC T-D curve through dynamic spiral CT scanning.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor angiogenesis plays a fundamental role in the pathogenesis of tumor growth and metastasis [1][2][3] , and significantly influences the biological behaviors of tumor and prognosis of patients [3][4][5][6] . The inhibition or blockade of this angiogenic activity, on the other hand, can slow down the tumor growth rate and positively affect the outcome of patients [7][8][9] .…”
Section: Introductionmentioning
confidence: 99%
“…54 Another study reported that plasma VEGF was a promising predictor for distant metastases from HCC. 55 The study reported that the levels were significantly elevated in the HCC group, compared with the control, chronic hepatitis, and cirrhosis groups. Furthermore, stage IV patients with distant metastases demonstrated significantly marked elevation of plasma VEGF compared with the patients at the other stages.…”
Section: Plasma Vegfmentioning
confidence: 96%